THERAPEUTIC MASSAGE TO TREAT NORMAL PHYSIOLOGICAL ANKLE AND FOOT EDEMA IN LATE PREGNANCY - Gloria Noble Khan; Shehla Naeem Zafar; Haider Ali; Inayatullah Khan; Alic William; Anila Jabeen; Naila Maqbool (International Journal of Contemporary Issues in Social Sciences, 2023)
Venous insufficiency leads to bilateral lower extremity edema in advancing healthy pregnancies affecting women’s quality of life by generating a variety of discomforts, the most of which are pain, cramps, and heaviness. The goal of the study was to collect evidence of how well therapeutic massage reduced the typical physiological edema of the ankle and foot that develops in late pregnancy. The study aimed to assess the effectiveness of therapeutic massage in reducing physiological ankle and foot edema during late pregnancy. Methods: A two-group randomized control trial was performed on 264 pregnant women between 28-38 weeks gestation devoid of any complication in outpatient clinics of a tertiary care hospital in Karachi, Pakistan. In each group, 132 participants were assigned to routine care and therapeutic massage groups through simple randomization. Results: The response rate was 90.2%. Both treatments were found significantly effective in reducing ankle and foot edema (p<0.0001) in late pregnancy. However, all bilateral mean measurements of the massage group confirmed greater decreases in edema as compared to the routine care group. Conclusion: Therapeutic massage was found to be a more effective and superior alternative to routine care to combat physiological lower extremity edema during late pregnancy.